Adhesives for on-site bonding: Characteristics, testing and prospects. (30th October 2015) - Pizzo, Benedetto; Smedley, Dave
Highlights: Products used on-site have specific characteristics different from other adhesives. Properties of epoxies, polyurethanes and PRF are related to industrial formulation. Testing methodologies specifically set-up for on-site adhesives are described. Effects related to long-term duration of loads are briefly reported. Future issues for on-site products which are of particular interest are introduced. Abstract: The manuscript deals with the main characteristics of those adhesives normally used for the reinforcement of timber structures, achieved through site-applied bonding. The characteristics relate to a combination of chemical composition and product formulation. A section describes testing procedures for products to be used on site, as this aspect does not exist in current European standards. The principal issues associated with the use of those products, mainly relating to long-term duration, are considered, focusing more on the adhesive characteristics rather than to the wood substrate properties. Finally, possible challenges are introduced in order to stimulate research in this field.